The Development of POPBUL (Pop-Up Badminton) to Improve Critical Thinking in Children Aged 5-6 Years - Lutfia Ananingrum; Kartika Rinakit Adhe; Dhian Gowinda Luh Safitri; Mallevi Agustin Ningrum (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to develop a learning medium called POPBUL (Pop‑Up Badminton) and evaluate its effectiveness in enhancing the critical‑thinking skills of children aged 5–6 years. The research was motivated by young learners’ low critical‑thinking ability and the lack of engaging, developmentally appropriate learning media. The ADDIE model—analysis, design, development, implementation, evaluation—guided the development process. Expert validation and field testing were conducted with 16 group‑B children at TK Dharma Siwi III Surabaya. Instruments included validation sheets, practicality questionnaires, and observation sheets administered before and after using the medium. POPBUL was rated very valid by media experts (87.5 %) and fairly valid by content experts (68.75 %); teacher practicality reached 93 %. Children’s mean score increased from 11.63 (pre‑test) to 16.63 (post‑test). A paired t‑test showed a significant difference (p = 0.000 < 0.05) with an n‑gain of 0.67 (moderate). Therefore, POPBUL is feasible and moderately effective for improving critical thinking in early childhood education.